2014
DOI: 10.3748/wjg.v20.i48.18458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial with traditional Chinese medicine intervention ''tonifying the kidney to promote liver regeneration and repair by affecting stem cells and their microenvironment'' for chronic hepatitis B-associated liver failure

Abstract: Treatment with "TTK" improved the survival rates of patients with liver failure due to chronic hepatitis B. Additionally, liver tissue was regenerated and liver function was restored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…30.72 AE 2.89 vs. 28.07 AE 4.56; P < 0.05)[12]. The results of the present study revealed that the mortality of 12.31% after the 8-week treatment was significantly lower in the RLR group than in the MMC group (50%) and CTW group (29.11%).…”
mentioning
confidence: 39%
“…30.72 AE 2.89 vs. 28.07 AE 4.56; P < 0.05)[12]. The results of the present study revealed that the mortality of 12.31% after the 8-week treatment was significantly lower in the RLR group than in the MMC group (50%) and CTW group (29.11%).…”
mentioning
confidence: 39%
“…2 , the biological processes and pathways involved by QXHC putative targets are often associated with the main therapeutic effects of the corresponding herbs. Especially, the herbs DG and CS have been indicated to play a role in activating blood circulation and enriching blood during the progression of menstrual disorders [ 17 ]; Accordingly, the putative targets of the two herbs were significantly associated with amyotrophic lateral sclerosis pathway, cardiac muscle contraction and various nutrient metabolic pathways, such as alanine, aspartate and glutamate metabolism, arginine and proline metabolism,as well as Glycine, serine and threonine metabolism; Herbs DS, TR, HH and CX function as ministerial drugs in QXHC, and has been found to exert synergistic effects with herbs DG and CS mainly in removing blood stasis and regulating blood circulation [ 18 20 ], in line with which, our enrichment analysis revealed that the putative targets of these herbs were involved into several hemopoiesis-related pathways, including amyotrophic lateral sclerosis, vascular smooth muscle contraction and VEGF signaling pathways; In the TCM theory, the main biological functions of the liver in human body is to regulate the circulation of “ qi ”, and the stagnation of “ qi ” often leads to the occurrence of diseases and depression [ 54 ]; Interestingly, our pathway enrichment analysis revealed that the putative targets of herbs CH, XF, YHS and JG were significantly associated with various emotion regulation-related pathways, such as long-term potentiation, long-term depression and neuroactive ligand-receptor interaction; It has been indicated that the adjunctive drugs WY and NX, and the messenger drug GC assist with DG and CS in nourishing the kidney and strengthening spleen for the treatment of menstrual disorders [ 24 26 ]. Here, we found that the putative targets of herbs DG, WY, NX, ZQ and GC were significantly associated with the pathways involved in the absorption and metabolism of various nutrients, including alanine, aspartate and glutamate metabolism, arginine and proline metabolism and phenylalanine metabolism; Moreover, the putative targets of ZQ may frequently play a role in immune modulation-related pathways, such as T/B cell receptor signaling pathways.…”
Section: Resultsmentioning
confidence: 80%
“…Selection and modification of appropriate herbal formulas based on patients' symptoms and signs are crucial. For instance, additions such as Chen Xiang (Agarwood), Dang Shen (Codonopsis), and processed Bai Zhu (Atractylodes) are used for poor appetite; Zhu Ru (Bamboo Shavings) is added for nausea and vomiting; Gan Jiang (Dried Ginger), Huang Qin (Scutellaria), and Huang Lian (Coptis) are added for diarrhea [14]. Clinical studies have shown that Ruan Gan Fang can effectively alleviate symptoms like poor appetite and abdominal distension [15].…”
Section: Chinese Herbal Medicine Treatmentmentioning
confidence: 99%